2015
DOI: 10.1007/s10858-015-9898-7
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR detects conformational change in the 100-kD membrane transporter ClC-ec1

Abstract: CLC transporters catalyze the exchange of Cl- for H+ across cellular membranes. To do so, they must couple Cl- and H+ binding and unbinding to protein conformational change. However, the sole conformational changes distinguished crystallographically are small movements of a glutamate side chain that locally gates the ion-transport pathways. Therefore, our understanding of whether and how global protein dynamics contribute to the exchange mechanism has been severely limited. To overcome the limitations of cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 117 publications
(164 reference statements)
0
23
0
Order By: Relevance
“…Interestingly, chlorideproton exchangers (ClCs) (6) were thought, until recently, to be an exception to this rule because transport seemed to be associated only with the local movements of side chains within a rigid protein scaffold (7)(8)(9). However, new data suggest that global structural transitions are also likely to be part of the ClC mechanism (10)(11)(12). It should be noted that small perturbations, such as mutations or the binding of small molecules, can turn some transporters into channels, presumably by stabilizing the states in which both the extracellular and intracellular gates are open (e.g., a double mutant of the Escherichia coli ClC transporter becomes a channel) (6,13,14).…”
Section: The Alternating-access Mechanismmentioning
confidence: 99%
“…Interestingly, chlorideproton exchangers (ClCs) (6) were thought, until recently, to be an exception to this rule because transport seemed to be associated only with the local movements of side chains within a rigid protein scaffold (7)(8)(9). However, new data suggest that global structural transitions are also likely to be part of the ClC mechanism (10)(11)(12). It should be noted that small perturbations, such as mutations or the binding of small molecules, can turn some transporters into channels, presumably by stabilizing the states in which both the extracellular and intracellular gates are open (e.g., a double mutant of the Escherichia coli ClC transporter becomes a channel) (6,13,14).…”
Section: The Alternating-access Mechanismmentioning
confidence: 99%
“…A central question, therefore, is whether and how other protein conformational changes contribute to the CLC transport mechanism. In previous work, we used a spectroscopic approach to evaluate conformational changes in CLC-ec1, and we found that raising [H + ] (to protonate Glu ex ) caused conformational change in regions of the protein outside of the permeation pathway, up to ~20 Å away from Glu ex (Elvington et al, 2009;Abraham et al, 2015). Using a combination of biochemical crosslinking, double electron-electron resonance (DEER) spectroscopy, functional assays, and molecular dynamics (MD) simulations, we concluded that this H + -induced conformational state represents an "outward-facing open" state, an intermediate in the transport cycle that facilitates anion transport to and from the extracellular side (Khantwal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A central question therefore is whether and how other 2 protein conformational changes contribute to the CLC transport mechanism. In previous work, we 3 used a spectroscopic approach to evaluate conformational changes in CLC-ec1, and we found that 4 raising [H + ] (to protonate Glu ex ) caused conformational change in regions of the protein outside of the 5 permeation pathway, up to ~20 Å away from Glu ex (Elvington et al, 2009;Abraham et al, 2015). 6…”
Section: Introductionmentioning
confidence: 99%